Confined interfacial micelle aggregating assembly of ordered macro–mesoporous tungsten oxides for H2S sensing. Issue 40 (9th October 2020) - Zhao, Tao; Fan, Yuchi; Sun, Ziqi; Yang, Jianping; Zhu, Xiaohang; Jiang, Wan; Wang, Lianjun; Deng, Yonghui; Cheng, Xiaowei; Qiu, Pengpeng; Luo, Wei
Abstract : 3D hierarchically porous WO3 has been constructed through confined interfacial micelle aggregating assembly approach. Owing to unique porous structure and crystalline frameworks, the obtained material shows excellent performance for detection of H2 S. Abstract : Porous tungsten oxides (WO3 ) have been implemented in various application fields including catalysis, energy storage and conversion, and gas sensing. However, the construction of hierarchically ordered porous WO3 nanostructures with highly crystalline frameworks remains a great challenge. Herein, a confined interfacial micelle aggregating assembly approach has been developed for the synthesis of ordered macro–mesoporous WO3 (OMMW) nanostructures using three-dimensional SiO2 photonic crystals (PCs) as nanoreactors for the confined assembly of tungsten precursor and poly(ethylene oxide)-block-polystyrene (PEO- b -PS) template. After the heat treatment and etching processes, the obtained OMMW could achieve hierarchically ordered porous nanostructures with close-packed spherical mesopores (∼34.1 nm), interconnected macro-cavities (∼420 nm), high accessible surface areas (∼78 m 2 g −1 ), and highly crystalline frameworks owing to the protection of dual templates. When OMMW nanostructures were assembled into gas sensors for the detection of H2 S, the resulting sensors exhibited excellent comprehensive sensing performance, including a rapid response–recovery kinetics, in addition to high selectivity and long-term stability, which are significantly better than the previously reported WO3 -based sensors. This study paves a promising way toward the development of hierarchically ordered porous semiconductors with large and interconnected porous channels for sensing applications.